Therapeutic advances in leiomyosarcoma - Lacuna, Kristine; Bose, Sminu; Ingham, Matthew; Schwartz, Gary (Frontiers in Oncology, 2023)
Leiomyosarcoma is an aggressive mesenchymal malignancy and represents one of the most common subtypes of soft tissue sarcomas. It is characterized by significant disease heterogeneity with variable sites of origin and diverse genomic profiles. As a result, the treatment of advanced leiomyosarcoma is challenging. First-line therapy for metastatic and/or unresectable leiomyosarcoma includes anthracycline or gemcitabine based regimens, which provide a median progression-free survival time of about 5 months and overall survival time between 14-16 months. Effective later-line therapies are limited. Molecular profiling has enhanced our knowledge of the pathophysiology driving leiomyosarcoma, providing potential targets for treatment. In this review, we explore recent advances in our understanding of leiomyosarcoma tumor biology and implications for novel therapeutics. We describe the development of clinical trials based on such findings and discuss available published results. To date, the most promising approaches for advanced leiomyosarcoma include targeting DNA damage repair pathways and aberrant metabolism associated with oncogenesis, as well as novel chemotherapy combinations. This review highlights the recent progress made in the treatment of advanced leiomyosarcoma. Ongoing progress is contingent upon further development of clinical trials based on molecular findings, with careful consideration for clinical trial design, strong academic collaborations, and prospective correlative analyses.